ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MEMAHAMI MASALAH SEGIEMPAT - Faradina, Apriliana Tezha Eka; Sunardi, Sunardi; Trapsilasiwi, Dinawati (Kadikma, 2016)
Abstract. Mathematics communication ability is the ability to present ideas to other people. Mathematics communication ability can be written and verbal. This research aimed to describe the student’s mathematics communication ability in understanding quadrilateral problems. The type of this research is descriptive qualitative research with the subjects of students class VIII SMPN 1 Jember amounted to 9 students who have categorized the ability of mathematics. Methods of data collection in this research are documentation, test and interviews. Based on the average from the test of written mathematics communication ability reinforced by interviews and tests of verbal mathematics communication ability, the ability of students' mathematics communication in understanding the quadrilateral problems are varied.. There are 4 students who have high mathematics communication ability, 2 students who have medium mathematics communication ability and 3 students who have low mathematics communication ability. Students who have high mathematics communication ability are able to fulfill 2-3 indicator of written mathematics communication ability (expressing and understanding mathematical ideas and use mathematical terms/notations) and 2-3 indicator of verbal mathematics communication ability (expressing and understanding mathematical ideas and use mathematical terms/notations). Students who have medium mathematics communication ability are able to fulfill 2 indicators of written mathematics communication ability ( understanding the mathematical ideas even if there are errors and use mathematical term/notations) and 2 indicators of verbal mathematics communication ability (expressing mathematical ideas and understanding mathematical ideas although there are still errors or using mathematical terms/notations). Students who have low mathematics communication ability are able to fulfill 1-2 indicator of written mathematics communication ability (understanding the mathematical ideas even if there are errors and use mathematical terms/notations) and 1 indicator of verbal mathematics communication ability (understanding mathematical ideas or use mathematical terms/notations even if there are errors). Keywords: Mathematics Communication Ability, Mathematical Ability, Quadriaterals